(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article talks about the classification of journalistic genres by various scientists, about the fact that from time immemorial the order of their division was almost the same, about the influence of the dierhisational management process on journalistic genres as well.